1998
DOI: 10.33584/jnzg.1998.60.2288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil fertility on the persistence of dryland cocksfoot and tall fescue pastures

Abstract: The persistence of pastures sown with tall fescue, cocksfoot or mixtures of the two species was evaluated by tiller core measurements on 106 paddocks that had been sown in 1989 or 1991 on dryland east coast sheep/beef farms. In both North and South Island paddocks, cocksfoot was the dominant grass in mixtures of tall fescue and cocksfoot. Tall fescue presence was usually much lower than that of ryegrass and other unsown grasses, regardless of sowing mixture. High levels of cocksfoot were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In 1996, a survey of beef and sheep pastures in the North Island showed that while cocksfoot tolerated low fertility, it responded well to high fertility, was more competitive and suppressed grasses such as browntop and sweet vernal, which grew best at lower fertility. However, at high fertility, cocksfoot also suppressed white clover and tall fescue (Schedonorus phoenix) (Festuca arundinacea) (Smith et al 1998). Similarly, in Waikato hill pastures grazed by cattle, there was an increase in ryegrass and white clover content and decline in weedy grasses, such as browntop, in response to increasing phosphorus application (Ledgard & Brier 1993).…”
Section: How Does Inter-specific Competition Influence Weed Ingress?mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, a survey of beef and sheep pastures in the North Island showed that while cocksfoot tolerated low fertility, it responded well to high fertility, was more competitive and suppressed grasses such as browntop and sweet vernal, which grew best at lower fertility. However, at high fertility, cocksfoot also suppressed white clover and tall fescue (Schedonorus phoenix) (Festuca arundinacea) (Smith et al 1998). Similarly, in Waikato hill pastures grazed by cattle, there was an increase in ryegrass and white clover content and decline in weedy grasses, such as browntop, in response to increasing phosphorus application (Ledgard & Brier 1993).…”
Section: How Does Inter-specific Competition Influence Weed Ingress?mentioning
confidence: 99%
“…Ninety-seven percent of the new pastures established well. This resulted in 112% more grazing and farmers reported greater animal production on the new pastures than the resident (mainly) perennial ryegrass-based pastures (Smith et al 1998). Greater drought tolerance and vigour of cocksfoot in a dryland system may also explain why the establishment of vulpia and soft brome (Bromus hordeaceus) was lower in cocksfoot than perennial ryegrass pastures in Canterbury, which is subject to hot, dry summers (Tozer et al 2010d).…”
Section: How Does Inter-specific Competition Influence Weed Ingress?mentioning
confidence: 99%
“…Over time, this leads to a dominance of weeds, and this can be an indicator of poor pasture persistence. Other grass species like cocksfoot have a reputation of being more tolerant of lower soil fertility, and being able to compete better with weeds, resulting in better persistence (Smith et al 1998). Production of cocksfoot however, is still responsive to increasing soil fertility (Smith et al 1998).…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Other grass species like cocksfoot have a reputation of being more tolerant of lower soil fertility, and being able to compete better with weeds, resulting in better persistence (Smith et al 1998). Production of cocksfoot however, is still responsive to increasing soil fertility (Smith et al 1998). Some alternative grasses to ryegrass have a similar or higher requirement for soil fertility (e.g.…”
Section: Soil Fertilitymentioning
confidence: 99%
See 1 more Smart Citation